Orang Kamoro: Perubahan Kehidupan dan Lingkungannya - Parsudi Suparlan (Antropologi Indonesia, 2001)
In this article, the author describes the history of changes among the Kamoro in Mimika. Some of the changes-due to changes in their physical, social, and cultural environment-were unexpected and surprising, so that they were not ready to cope with. Consequently, there were two prominent implications in their life: the increase of consumerism behavior, and the occurrence of more frequent conflicts among themselves. In the final part, the author examines the Kamoro relationship with outsiders, of how they categorize the latter, and with whom they used to generate conflicts. Recently, conflicts mainly occur on the problems of land dispute with outsiders, and in the competition to get the 'one million-dollars' funds from PT Freeport.